PENGAMBILAN TELUR DARI INDUK NILA MERAH (Oreochromis sp.) PENGARUHNYA TERHADAP KECEPATAN BERPIJAH KEMBALI - Rustadi Rustadi (Universitas Gadjah Mada, 1996)
Removing eggs from red nila female during spawning period were observed to know an appropriate time of removal and its effect on inter-spawning period of female broodstock. Spawning experiment was conducted with three replicates in the hapa. The female that cared fertilized eggs were cathed on 7th day, 21th, 28th day, and 35th day after stocking. Other spawning experiment with three relications were cared out to test the effect of removing eggs. On 7th day after spawning produced the highest number of spawned female reduced yhe inter-spawning interval, but there was no effect of male stocking on re-spawning rate of female. The low number of eggs per spawner together with asynchronus spawning would be problems faced on mass production of red nila seed.